THE INFLUENCE OF CUSTOMER VALUE, CUSTOMER EXPERIENCE ON CUSTOMER LOYALTY MEDIATED BY CUSTOMER SATISFACTION - Tumbel, Brillian; Lapian, S.L.H.V. Joyce; Rogi, Mirah H. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
This research investigates the influence of customer value and customer experience on customer loyalty, with a specific focus on the mediating role of customer satisfaction. In an increasingly competitive market, understanding the dynamics of customer loyalty is essential for businesses aiming to enhance their market position. The study employs a quantitative explanatory research approach, utilizing surveys and questionnaires to gather data from respondents. The research aims to analyze the direct effects of customer value and experience on customer satisfaction and loyalty, as well as the indirect effects mediated by customer satisfaction. The findings are expected to provide valuable insights for business owners, enabling them to design effective strategies that enhance customer value and experience, ultimately fostering greater customer loyalty. This research not only contributes to the theoretical understanding of customer loyalty dynamics but also offers practical implications for businesses seeking to improve their customer relationship management practices. The results are anticipated to serve as a foundation for future studies in the field of marketing and customer behavior. . Keywords: Customer Value, Customer Experience, Customer Loyalty, Customer Satisfaction